Computational Intelligence and Human- Computer Interaction: Modern Methods and Applications - Cojocar, Grigoreta-Sofia; Guran, Adriana-Mihaela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book contains all of the articles that were accepted and published in the Special Issue of MDPI's journal Mathematics titled "Computational Intelligence and Human-Computer Interaction: Modern Methods and Applications". This Special Issue covered a wide range of topics connected to the theory and application of different computational intelligence techniques to the domain of human-computer interaction, such as automatic speech recognition, speech processing and analysis, virtual reality, emotion-aware applications, digital storytelling, natural language processing, smart cars and devices, and online learning. We hope that this book will be interesting and useful for those working in various areas of artificial intelligence, human-computer interaction, and software engineering as well as for those who are interested in how these domains are connected in real-life situations.